The aircraft designers : a Grumman historical perspective - Ciminera, Michael V.; Grumman, Nothrop (Library of flight., 2013)
This book tells the behind-the-scenes story of the designers and engineers who conceived and built Grumman aircraft from the founding of the company in 1929 until its 1994 acquisition by Northrop. It focuses on the people, disciplines, processes, and anecdotes behind the creation of such past icons as the F6F Wildcat and TBF Avenger and modern-day weapon systems like the F-14 Tomcat, E-2 Hawkeye, EA-6B Prowler, and Joint STARS. The author identifies key team members who contributed to the creation and development of each new design, creating an unparalleled historical record of the aeronautical achievements of the Grumman Corporation and he chronicles the evolution from the aircraft design of the past, which bore the earmark of the chief engineer/designer, to today's complex aircraft systems, which require a significant team effort involving such disciplines as aerodynamics, structures, propulsion, avionics, systems analysis, software, simulation, and testing. --